2002
DOI: 10.1176/appi.ajp.159.9.1576
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders Among U.S. Military Personnel in the 1990s: Association With High Levels of Health Care Utilization and Early Military Attrition

Abstract: Mental disorders appear to represent the most important source of medical and occupational morbidity among active-duty U.S. military personnel. These findings provide new population-based evidence that mental disorders are common, disabling, and costly to society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
164
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 251 publications
(176 citation statements)
references
References 34 publications
10
164
2
Order By: Relevance
“…It is also possible that individuals diagnosed with nondependent abuse of drugs and other mental disorders feel a certain degree of social stigmatization and prefer not to share their health information with strangers. For example, Hoge et al documented that some military members are likely to avoid seeking health care for mental disorders due to perceived concerns over the social stigmatization and the possible adverse impact mental disorder diagnoses may have on careers [29,30]. It is also plausible that those with adjustment reactions felt overwhelmed at the time of invitation and felt that they were unable to add additional responsibilities, such as committing to a 21-year follow-up, thus making them less likely to respond.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that individuals diagnosed with nondependent abuse of drugs and other mental disorders feel a certain degree of social stigmatization and prefer not to share their health information with strangers. For example, Hoge et al documented that some military members are likely to avoid seeking health care for mental disorders due to perceived concerns over the social stigmatization and the possible adverse impact mental disorder diagnoses may have on careers [29,30]. It is also plausible that those with adjustment reactions felt overwhelmed at the time of invitation and felt that they were unable to add additional responsibilities, such as committing to a 21-year follow-up, thus making them less likely to respond.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors unique to the Armed Forces that affect confidentiality and trust, such as the apparent stigma within some Units of reporting to 'sick parade', and the integrity and confidentiality within the chain of command. 18 We are currently facing a general lack of confidence in public institutions as a whole, and that includes both medicine and the Armed Forces. 3,19,20 As O'Neill stated, whether mistrust is well founded or not, it has a debilitating impact on society.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] One study that was conducted just before the military operations in Iraq and Afghanistan began found that at least 6 percent of all U.S. military service members on active duty receive treatment for a mental disorder each year. 9 Given the ongoing military operations in Iraq and Afghanistan, mental disorders are likely to remain an important health care concern among those serving there.…”
mentioning
confidence: 99%